The magnetic anal sphincter in faecal incontinence: is initial success sustained over time?. (December 2013) - Barussaud, M.‐L.; Mantoo, S.; Wyart, V.; Meurette, G.; Lehur, P.‐A.
Abstract Aim In the short term, implantation of a magnetic anal sphincter (MAS) is a safe and effective treatment for faecal incontinence (FI). In this paper we show that the initial results stand the test of time and patient satisfaction remains high in the medium term. Method Data on 23 women [median age 64 (35–78) years] implanted with a MAS device between December 2008 and September 2012 were reviewed from a prospective database. Assessment was based on significant improvement of incontinence scores – the Cleveland Clinic Florida Incontinence Severity (CCF‐IS) score, Faecal Incontinence Quality of Life (FIQoL) score – and patient satisfaction at 6, 12, 24 and 36 months after surgery. Results The device was removed in two patients owing to complications. Median follow‐up was 17.6 months. The median preoperative CCF‐IS score was 15.2 and fell to 6.9, 7.7, 7.8 and 5.3 at 6, 12, 24 and 36 months, respectively. The median FIQoL score significantly (P < 0.001) improved from 1.97 preoperatively to 3.19, 3.11, 2.92 and 2.93, respectively, at the same time periods. The concordance of the CCF‐IS and FIQoL scores was 91%. Sixteen of the 23 patients were satisfied but only 14 would have recommended the MAS to someone else. Lack of improvement was the main reason for dissatisfaction. Conclusion Good initial results tend to remain stable over time and about two‐thirds of patients are satisfied after MAS implantation.